TEACHER’S QUESTIONS IN EFL CLASSROOM INTERACTION - Vebriyanto, Danu Angga (Vision: Journal for Language and Foreign Language Learning, 2015)
Questioning is a basic method implemented by teacher in orderto build interaction in the classroom and also to stimulate the stu-dents to perform their speaking skill in target language. The presentstudy attempted to describe the types of questions that the teacherusually applies in the classroom during teaching and learning pro-cess, to fi nd out the teacher’s purposes of applying those levels ofquestioning, and to describe the effects of applying the levels ofquestioning for the students’ understanding of English, and to iden-tify students’ oral responses towards teacher questions. The datawere collected by recording the teaching and learning process andinterviewing the English teacher. Based on the research fi ndings, itwas discovered that the teacher utilized certain types of questions.Referential-open questions that can elicit longer responses were31%. On the other hand, the percentage of display-closed questionswas 69%. Questions that are categorized as display/closed ques-tions were widely used for checking students’ understanding of thematerials questions that categorized as referential/open questionswere widely used for looking for certain information from the stu-dents. It was found that in all season 70% of students’ responseswere in form of words. The production of words was the effect ofemploying display or closed question. In the other hand, students’responses in form of sentence were 7 sentences. It was the effect ofemploying referential or open question.